الوقت في العمل المؤسسي: قيمته وأساليب إدارته - شناف، خديجة Shannaf, Khadijah (جامعة قاصدي مرباح - ورقلة, 2017)
Time is considered one of the most important elements of the institutional work; the unexploited makes enterprises pay tax expensive, Overstepping that resorted to contemporary institutions to time management in order to accomplish the tasks smoothly and without pressure, with minimal effort. Time management skill grow the practice, is to develop the capacity of individuals to choose methods and tools to suit the nature of their work, taking into account that the problem does not lie in the lack of time; but in his way. In this article will be highlighted: the types of time at work, the advantages of good management and time-consuming, the influential factors in its estimates of the methods of his administration in institutional work in a better way.
يعتبر الوقت أهم عناصر العمل المؤسسى؛ حيث أن عدم استغلاله يجعل المؤسسات تدفع الضريبة غالية، ولتجاوز ذلك لجأت المؤسسات المعاصرة إلى إدارة الوقت لتتمكن من انجاز المهام بيسر ودون ضغوط. وبأقل جهد. وإدارة الوقت مهارة تنمو بالممارسة، فهي تنمي قدرة الأفراد على اختيار الأساليب والأدوات الثى تناسب طبيعة عملهم، مع الأخذ بعين الاعتبار أن المشكلة لا تكمن في عدم وجود الوقت؛ بل في طريقة إدارته. وفي هذا المقال سيتم تسليط الضوء على: أنواع الوقت في العمل، مزايا الإدارة الجيدة للوقت، العوامل المؤثرة في تقديراته وأساليب إدارته في العمل المؤسسي بطريقة أفضل.
Keywords: الأداء المؤسسي -- إدارة الوقت -- اتخاذ القرار